C&V : Seventy-eighth : Exhibition by Artists of Chicago and Vicinity. - The Art Institute of Chicago (Chicago : The Art Institute of Chicago, 1980)
Axeman, James F. ; Bramson, Phyllis ; Buglewicz, Michael J. ; Clearfield, Bruce ; Denlinger, Thomas ; Dohner, Markus ; Hild, Nancy ; Hull, Richard ; Ito, Miyoko ; Kramer, Linda L. ; Lauerman, Ardith ; McCauley, Robert N. ; McCreedy, Marion ; Monaco, Clar ; Mose, Steve ; Redick, Pamela Lang ; Rossi, Barbara ; Santiago, Filemon ; Sigler, Hollis ; Simpson, Diane ; Spiggle, Gregory C. ; etc.
C&V : Seventy-eighth : Exhibition by Artists of Chicago and Vicinity, The Art Institute of Chicago, November 29, 1980 through January 4, 1981
boek